2012 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2012
DOI: 10.1109/embc.2012.6347009
|View full text |Cite
|
Sign up to set email alerts
|

The auditory p300-based SSBCI: A door to minimally conscious patients?

Abstract: In this study we report on the evaluation of a novel auditory single-switch BCI in nine patients diagnosed with MCS. The task included a simple and a complex oddball paradigm, the latter uses the tone stream segregation phenomenon. In all patients a significant difference between deviant and frequent tones could be observed in EEG. However, in some cases the deviant tones produce a significant negative peak and in some a very late positive peak. These preliminary findings are relevant in order to address futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
(18 reference statements)
0
14
0
Order By: Relevance
“…Our main question was, whether a paradigm that is promising in healthy subjects can also successfully be applied to MCS patients. Some preliminary results of this work have already been presented in [30].…”
Section: Introductionmentioning
confidence: 92%
“…Our main question was, whether a paradigm that is promising in healthy subjects can also successfully be applied to MCS patients. Some preliminary results of this work have already been presented in [30].…”
Section: Introductionmentioning
confidence: 92%
“…As regard P3, it could be obtained in 20-25 % of DoC patients (Witzke and Schönle 1996 ; Kotchoubey et al 2001Kotchoubey et al , 2005Cavinato et al 2009 [only traumatic VS/UWS patients], Schnakers et al 2008 [P3 found only in MCS but not in VS/UWS], Müller-Putz et al 2012 ;Guger et al 2013 ;Steppacher et al 2013 ). This may indicate activation of complex cortico-subcortical networks in response to target stimuli in many patients.…”
Section: Erp Manifest Remaining Cognitive Processes In Doc Patientsmentioning
confidence: 98%
“…As argued in (Lotte et al 2018), no signal analysis techniques would be able to recognize (decode) specific command patterns if the user is unable to produce (encode) them. For example, the subject could be: unable to receive an input from the system (stimulus, feedback or information about the state of the BCI); potentially alarmed or scared by the stimulus (Schreuder, Blankertz, and Tangermann 2010;Müller-Putz et al 2012); unable to focus on the required mental task; unable to continuously focus on the assigned task. The inconstancy of the user mood, stress, engagement, and level of attention is also a cause of the BCI performance variability and should be taken in account (Friedrich et al 2015;Pammer-Schindler et al 2017).…”
Section: Bci Illiteracymentioning
confidence: 99%